Interactive typology tool for spatial targeting of FNS interventions - Marivoet, Wim; Ulimwengu, John M. (International Food Policy Research Institute, 2023)
In this interactive we develop a typology to help design and improve spatial targeting of food and nutrition security (FNS) interventions. Based on the efficiency estimation within a four-indicator diagram which represent the core segments of a food system, the proposed approach allows for the broad identification and location of major FNS bottlenecks. After discussing the basic concepts, we illustrate the core typology using a real-world example and propose a series of extensions to further refine its approach for improved policymaking.